Negative electrode for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery having the same
By using porous metal bodies and silicon-based materials in the negative electrode of the nonaqueous electrolyte secondary battery and improving the permeability of the skeleton forming agent, the problems of negative electrode film thickness limitation and durability are solved, and the energy density is improved and the cycle durability is achieved. Improvement of sexuality.
Patent Information
- Application Number
- CN202210106467.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-02-01
- Filing Date
- 2022-01-28
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-01-28
AI Technical Summary
The film thickness limitations of the negative electrode of the existing non-aqueous electrolyte secondary battery during the production process, which makes it difficult to improve the energy density. At the same time, the unbalanced adhesion of the adhesive and the expansion and contraction of the negative electrode active material lead to durability problems.
A porous metal body is used as the current collector, and the negative electrode active material and a skeleton forming agent composed of a silicon-based material are filled in the pores. By improving the permeability of the skeleton forming agent, the electrode structure deterioration is suppressed and cycle durability is improved.
By improving the permeability of the skeleton forming agent, the electrode structure deterioration is suppressed, the circulation durability is improved, and the energy density of the battery is enhanced.
Smart Images

Figure CN114843490B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a negative electrode for a non-aqueous electrolyte secondary battery and a non-aqueous electrolyte secondary battery having the negative electrode. Background Art
[0002] In recent years, non-aqueous electrolyte secondary batteries such as lithium ion secondary batteries are not only small and light, but also can obtain high power, so their use in automobiles, etc. is increasing. Non-aqueous electrolyte secondary batteries are battery systems in which electrolytes are not based on water as the main component and are a general term for storage devices that can be charged and discharged. For example, lithium ion batteries, lithium polymer batteries, all-solid-state lithium batteries, lithium-air batteries, lithium-sulfur batteries, sodium ion batteries, potassium ion batteries, multivalent ion batteries, fluoride batteries, sodium-sulfur batteries, etc. are known. The non-aqueous electrolyte secondary battery is mainly composed of a positive electrode, a negative electrode, and an electrolyte. Moreover, when the electrolyte has fluidity, a diaphragm is further inserted between the positive electrode and the negative electrode to form.
[0003] For example, for the purpose of improving battery life, the following technology is disclosed: a skeleton forming agent containing a silicate having a siloxane bond is present at least on the surface of an active material, and the skeleton forming agent is allowed to penetrate from the surface to the inside (for example, refer to Patent Document 1). According to this technology, a strong skeleton can be formed for the active material, so it is believed that the battery life can be improved. In addition, a technology for applying the above-mentioned skeleton forming agent to a negative electrode containing a silicon (Si)-based active material is also disclosed (for example, refer to Patent Document 2).
[0004] [Prior art literature]
[0005] [Patent Document]
[0006] [Patent Document 1] Japanese Patent No. 6369818
[0007] [Patent Document 2] Japanese Patent No. 6149147 Summary of the invention
[0008] [Problems to be solved by the invention]
[0009] In addition, for the above-mentioned nonaqueous electrolyte secondary battery, it is required to improve the energy density. In order to improve the energy density, it is considered effective to increase the film thickness of the negative electrode or to make the negative electrode active material high-density. However, the prior art has a limit on the thickness of the negative electrode in the manufacture of the negative electrode. Specifically, the practical thickness of the film thickness that the composite layer can be applied to the existing collector foil is less than 100μm. If the film thickness is more than 100μm, problems such as uneven coating, cracking, and peeling will occur, and it is difficult to manufacture the negative electrode with high precision.
[0010] In addition, due to the balance between the binding force of the binder and the expansion and contraction of the negative electrode active material, there is a limit to the amount of negative electrode active material per unit area from the perspective of durability. Specifically, the limit of the capacity of the negative electrode active material per unit area is 4 mAh / cm 2 (film thickness is 50 μm). If it is more, sufficient cyclability cannot be guaranteed. On the other hand, if the active material capacity is less than 4 mAh / cm 2 , we cannot expect an increase in energy density.
[0011] In order to solve the above problems, it is considered that the collector of the negative electrode of the non-aqueous electrolyte secondary battery is applied with a porous metal body, and the electrode composite is filled in the porous metal body. It is known that in the non-aqueous electrolyte secondary battery, when the negative electrode is applied with a collector composed of a porous metal body, the negative electrode active material is applied with an electrode active material composed of a silicon-based material and a skeleton forming agent is applied to coat the collector and the electrode active material, the inorganic binder will not penetrate into the pores of the collector. In addition, it is also known that the non-aqueous electrolyte secondary battery using such a negative electrode will deteriorate structurally inside the electrode due to repeated charging and discharging, and thus the battery performance will deteriorate.
[0012] Therefore, it is desired to have a negative electrode for a non-aqueous electrolyte secondary battery and a non-aqueous electrolyte secondary battery having the negative electrode, which can suppress structural degradation of the electrode and improve cycle durability by increasing the permeability of a skeleton forming agent into a current collector composed of a porous metal body.
[0013] The present invention is completed in view of the above content, and its purpose is to provide a negative electrode for a non-aqueous electrolyte secondary battery and a non-aqueous electrolyte secondary battery equipped with the negative electrode, which can inhibit the structural degradation of the electrode and improve the cycle durability by increasing the permeability of the skeleton forming agent into the interior of the collector composed of a porous metal body.
[0014] [Methods of solving the problem]
[0015] (1) In order to achieve the above-mentioned purpose, the present invention provides a negative electrode for a non-aqueous electrolyte secondary battery, which comprises: a collector composed of a porous metal body; a first negative electrode material, which is arranged in the pores of the porous metal body and has a negative electrode active material composed of a silicon-based material, a conductive aid and a binder; and a second negative electrode material, which is arranged in the pores of the porous metal body and has a skeleton former, and the skeleton former includes a silicate with a siloxane bond; and the negative electrode for a non-aqueous electrolyte secondary battery has: a pair of first regions, which are formed on both outer sides of the collector in the thickness direction and are provided with the first negative electrode material and the second negative electrode material; and a second region, which is formed in the center of the collector in the thickness direction and is provided with the second negative electrode material instead of the first negative electrode material.
[0016] (2) In order to achieve the above-mentioned purpose, the present invention also provides a negative electrode for a non-aqueous electrolyte secondary battery, which comprises: a collector composed of a porous metal body; a first negative electrode material, arranged in the pores of the porous metal body and having a conductive additive; a second negative electrode material, arranged in the pores of the porous metal body and having a negative electrode active material and a binder composed of a silicon-based material; and a third negative electrode material, arranged in the pores of the porous metal body and having a skeleton former, wherein the skeleton former comprises a silicate having a siloxane bond; and the negative electrode for a non-aqueous electrolyte secondary battery comprises: a pair of first regions, formed on both outer sides of the collector in the thickness direction and arranged with the first negative electrode material, the second negative electrode material and the third negative electrode material; and a second region, formed in the center of the collector in the thickness direction and arranged with the first negative electrode material and the third negative electrode material without arranging the second negative electrode material.
[0017] (3) In the negative electrode for a nonaqueous electrolyte secondary battery of (1) or (2), the skeleton-forming agent may include a silicate represented by the following general formula (1).
[0018] [Chemistry 1]
[0019] A 2 O·nSiO 2 ……Formula (1)
[0020] [In the general formula (1), A represents an alkali metal]
[0021] (4) In the negative electrode for a nonaqueous electrolyte secondary battery according to any one of (1) to (3), the thickness of the second region may be 0.5 to 15% of the thickness of the entire negative electrode.
[0022] (5) In the negative electrode for a nonaqueous electrolyte secondary battery according to any one of (1) to (4), the porous metal body may be a foamed metal body.
[0023] (6) The present invention also provides a nonaqueous electrolyte secondary battery comprising the negative electrode for a nonaqueous electrolyte secondary battery according to any one of (1) to (5).
[0024] [Effects of the Invention]
[0025] According to the present invention, a negative electrode for a nonaqueous electrolyte secondary battery and a nonaqueous electrolyte secondary battery having the negative electrode can be provided, which can suppress durability degradation by increasing the permeability of a skeleton forming agent into a current collector composed of a porous metal body and can increase energy density. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a diagram schematically showing the internal structure of the negative electrode for a non-aqueous electrolyte secondary battery according to the first embodiment of the present invention.
[0027] Figure 2 It is a diagram schematically showing the structure of a negative electrode for a nonaqueous electrolyte secondary battery according to a second embodiment of the present invention.
[0028] Figure 3 This is a schematic diagram showing a state in which a negative electrode material is filled into a current collector composed of a porous metal body to produce a negative electrode layer precursor in the first embodiment of the present invention.
[0029] Figure 4 This is a schematic diagram showing that in the first embodiment of the present invention, a skeleton forming agent is impregnated into Figure 1 A diagram showing the situation of manufacturing a negative electrode for a non-aqueous electrolyte secondary battery by using a negative electrode layer precursor.
[0030] Figure 5 This is a schematic diagram showing a state in which a negative electrode layer precursor is manufactured by filling a current collector composed of a porous metal body with a second conductive auxiliary agent and then filling it with a negative electrode material in the second embodiment of the present invention.
[0031] Figure 6 This is a schematic diagram showing that in the second embodiment of the present invention, a skeleton forming agent is impregnated into Figure 2 A diagram showing the situation of manufacturing a negative electrode for a non-aqueous electrolyte secondary battery by using a negative electrode layer precursor.
[0032] Figure 7 This is a graph showing the relationship between the number of cycles and the discharge capacity of Examples 1 and 2 and Comparative Example 1. DETAILED DESCRIPTION
[0033] <First embodiment>
[0034] Below, while referring to the attached Figure 1 The first embodiment of the present invention will be described in detail.
[0035] [negative electrode]
[0036] Figure 1 1 is a diagram schematically showing the internal structure of the negative electrode for a non-aqueous electrolyte secondary battery of the present invention. The negative electrode for a non-aqueous electrolyte secondary battery 1 of the present embodiment comprises: a current collector 11, which is composed of a porous metal body; a first negative electrode material 12, which is arranged in the pores of the porous metal body and has a negative electrode active material 13 composed of a silicon-based material, a conductive auxiliary agent 15 and a binder 16; and a second negative electrode material 19, which is arranged in the pores of the porous metal body and has a skeleton forming agent 14, and the skeleton forming agent 14 contains a silicate having a siloxane bond.
[0037] The negative electrode 1 for a non-aqueous electrolyte secondary battery of this embodiment has on the collector 11: a pair of first regions 17 formed on both outer sides in the thickness direction of the collector 11 and arranged with a first negative electrode material 12 and a second negative electrode material 19; and a second region 18 formed in the center in the thickness direction of the collector and arranged with the second negative electrode material 19 instead of the first negative electrode material 12.
[0038] For example, by applying the present embodiment to a negative electrode for a lithium ion secondary battery, a negative electrode for a lithium ion secondary battery and a lithium ion secondary battery having the negative electrode can be provided, which can suppress the endurance degradation and the structural degradation of the electrode by increasing the permeability of the skeleton forming agent into the collector composed of a porous metal body, and can improve the energy density and cycle durability. Below, an example of applying the present embodiment to a negative electrode for a lithium ion secondary battery is described in detail, and various additions, changes or deletions can be made without departing from the scope of the present invention.
[0039] As the current collector 11, a current collector composed of a porous metal body is used. Examples thereof include a mesh, a woven fabric, a non-woven fabric, an embossed body, a punched body, an expanded body, a foamed body, and the like, and a foamed metal body is preferably used. Among them, a foamed metal body having a three-dimensional network structure with continuous pores is preferably used, and for example, Celmet (registered trademark) (manufactured by Sumitomo Electric Industries, Ltd.) and the like can be used.
[0040] The material of the porous metal body is not particularly limited as long as it has electronic conductivity and can conduct electricity to the electrode material held therein. For example, conductive metals such as Al, Al alloys, Ni, Ni-Cr alloys, Fe, Cu, Ti, Cr, Au, Mo, W, Ta, Pt, Ru, and Rh, and conductive alloys containing two or more of these conductive metals (stainless steel (SUS304, SUS316, SUS316L, YUS270, etc.)) can be used. In addition, when a material other than the above-mentioned conductive metals or conductive alloys is used, for example, a multilayer structure in which different metals such as Cu or Ni are coated on Fe can be used. Among them, Ni or a Ni alloy is preferably used because of its excellent electronic conductivity and reduction resistance.
[0041] The thickness of the porous metal body is preferably 10 μm or more, more preferably 50 μm or more. The thickness of the porous metal body is preferably 1 mm or less, more preferably 800 μm or less.
[0042] The average pore size of the porous metal body before pressurization is preferably 100 μm to 850 μm. By making the average pore size of the porous metal body within this range, the distance between the negative electrode active material 13 filled or supported inside the porous metal body and the metal skeleton is stabilized, the electronic conductivity is improved, and the increase in the internal resistance of the battery is suppressed. Moreover, even if the volume changes with charging and discharging, the shedding of the electrode composite agent can be suppressed.
[0043] The specific surface area of the porous metal body is preferably 1000 to 10000 m 2 / m 3 This is 2 to 10 times the specific surface area of conventional collector foils. By making the specific surface area of the porous metal body within this range, the contact between the electrode composite and the collector 11 is improved, thereby suppressing the increase in the internal resistance of the battery. A more preferred specific surface area is 4000 to 7000 m 2 / m 3 .
[0044] The porosity of the porous metal body is preferably 90 to 99%. By making the porosity of the porous metal body within this range, the filling amount of the electrode composite can be increased, thereby improving the energy density of the battery. Specifically, if the porosity exceeds 99%, the mechanical strength of the porous metal body will significantly decrease, and it is easy to be damaged due to the volume change of the electrode accompanying the charge and discharge. On the contrary, if it is less than 90%, not only the filling amount of the electrode composite decreases, but also the ion conductivity of the electrode decreases, and it becomes difficult to obtain sufficient input and output characteristics. From these viewpoints, the more preferred porosity is 93 to 98%.
[0045] The electrode weight per unit area of the porous metal body is preferably 1 to 100 mg / cm 2 By making the electrode unit area weight of the porous metal body within this range, the active material capacity can be fully realized, and the electrode can show the designed capacity. The more preferred electrode unit area weight is 5 to 60 mg / cm 2 .
[0046] As the negative electrode active material 13, a material that can reversibly absorb and release lithium ions is used. Specifically, a negative electrode active material composed of a high-capacity silicon-based material is used. As silicon-based materials, there are silicon alone, silicon alloys, silicon oxides, silicon compounds, etc. Here, the so-called silicon alone refers to crystalline or amorphous silicon with a purity of 95% by mass or more. The so-called silicon alloy refers to a Si-M alloy composed of silicon and other transition elements M. M can be, for example, Al, Mg, La, Ag, Sn, Ti, Y, Cr, Ni, Zr, V, Nb, Mo, etc. It can also be a complete solid solution alloy, eutectic alloy, hypoeutectic alloy, hypereutectic alloy, peritectic alloy. The so-called silicon oxide refers to an oxide of silicon or a silicon alone component and SiO 2The composite body can be formed by the element ratio of Si to O as long as the ratio of Si to O is 1 or less than 1.7. The so-called silicon compound is a substance formed by chemical bonding of silicon with two or more other elements. Among them, silicon alone is preferred in terms of being able to form a good interface layer described later. Alternatively, a substance in which a carbon material is mixed or compounded in a silicon material can also be used.
[0047] The shape of the silicon-based material is not particularly limited, and may be spherical, elliptical, faceted, ribbon-shaped, fibrous, flaky, toroidal, or hollow powder. These may be single particles or granules.
[0048] The negative electrode active material 13 made of silicon material has an expansion coefficient of 10% or more during charge and discharge. That is, the negative electrode active material 13 expands and contracts greatly during charge and discharge. By using the skeleton forming agent 14 described below, the durability degradation caused by the expansion and contraction can be suppressed.
[0049] From the viewpoint of achieving excellent cycle characteristics of the electrode and obtaining high input-output characteristics, the particle size of the silicon-based material is preferably 1.0 μm to 15 μm.
[0050] In the present embodiment, the second negative electrode material 19 includes a skeleton-forming agent 14 .
[0051] The skeleton forming agent 14 includes a silicate having a siloxane bond. More specifically, the skeleton forming agent 14 preferably includes a silicate represented by the following general formula (1).
[0052] [Chemistry 2]
[0053] A 2 O·nSiO 2 ……Formula (1)
[0054] In the above general formula (1), A represents an alkali metal. Among them, preferably A is at least one of lithium (Li), sodium (Na) and potassium (K). By using such an alkali metal silicate having a siloxane bond as a skeleton forming agent, a lithium ion secondary battery with high strength, excellent heat resistance and excellent cycle life can be obtained.
[0055] In addition, in the above general formula (1), n is preferably greater than 1.6 and less than 3.9. By making n within this range, when the skeleton forming agent 14 is mixed with water to form a skeleton forming agent liquid, a moderate viscosity can be obtained, and when the skeleton forming agent 14 is applied to the negative electrode containing silicon as the negative electrode active material 13 as described later, it is easy to penetrate into the negative electrode material 12. Therefore, a lithium ion secondary battery with high strength, excellent heat resistance and excellent cycle life can be obtained more reliably. A more preferred n is greater than 2.0 and less than 3.5.
[0056] The silicate is preferably amorphous. Since amorphous silicates are composed of disordered molecular arrangements, they do not break in a specific direction like crystals. Therefore, by using amorphous silicates as the skeleton forming agent 14, the cycle life characteristics are improved.
[0057] For example, by applying the above-mentioned skeleton forming agent liquid to the negative electrode containing silicon as the negative electrode active material 13, the skeleton forming agent 14 will penetrate between the negative electrode active materials 13. Therefore, it is speculated that the silicon constituting the negative electrode active material 13 and the above-mentioned silicate constituting the skeleton forming agent 14 will fuse, for example, the hydrolyzed silicate undergoes a dehydration reaction (condensation reaction of silanol groups) by heating, thereby forming a siloxane bond (-Si-O-Si-). That is, in the negative electrode 1 for lithium-ion secondary batteries of the present embodiment, an interface layer composed of inorganic substances is formed at the interface between the negative electrode active material 13 and the skeleton forming agent 14, and the interface layer contains silicon derived from siloxane bonds and alkali metals generated by hydrolysis of silicates, etc. Moreover, it is speculated that through the presence of this interface layer, the negative electrode active material 13 and the skeleton forming agent 14 will be firmly combined, resulting in excellent cycle life characteristics.
[0058] In this embodiment, the ratio of alkali metal atoms in the interface layer to all constituent atoms is preferably higher than the ratio of alkali metal atoms in the skeleton forming agent 14 to all constituent atoms. More specifically, the ratio of alkali metal atoms in the interface layer to all constituent atoms is preferably 5 times or more of the ratio of alkali metal atoms in the skeleton forming agent 14 to all constituent atoms. Thereby, the bond between the negative electrode active material 13 and the skeleton forming agent 14 becomes stronger, and the peeling or wrinkling or cracking of the collector 11 caused by the expansion and contraction of the negative electrode active material 13 during charge and discharge is further suppressed, thereby further improving the cycle life.
[0059] The thickness of the interface layer is preferably 3 to 30 nm. By making the thickness of the interface layer within this range, the bond between the negative electrode active material 13 and the skeleton forming agent 14 becomes stronger, and the expansion and contraction of the negative electrode active material 13 during charge and discharge, which may cause peeling or wrinkling or cracking of the collector 11, is further suppressed, thereby further improving the cycle life.
[0060] The skeleton forming agent 14 of this embodiment may also contain a surfactant. Thereby, the lyophilicity of the skeleton forming agent 14 into the first negative electrode material 12 is improved, and the skeleton forming agent 14 will uniformly penetrate into the negative electrode material 12. Therefore, a uniform skeleton is formed between the negative electrode active materials 13 in the negative electrode material 12, and the cycle life characteristics will be further improved.
[0061] In the present embodiment, the content (density) of the skeleton forming agent 14 relative to the total of the first negative electrode material 12 and the second negative electrode material 19 is preferably 0.5 to 2.0 mg / cm 2 When the content of the skeleton-forming agent 14 relative to the total of the first negative electrode material and the second negative electrode material is within this range, the effect of using the skeleton-forming agent 14 can be more reliably exerted.
[0062] When the total solid content of the negative electrode active material 13, the skeleton forming agent 14, the conductive auxiliary agent 15 and the binder 16 is set to 100% by mass, the content of the skeleton forming agent 14 is preferably 3.0 to 40.0% by mass. If the content of the skeleton forming agent 14 is within this range, the effect of using the above-mentioned skeleton forming agent 14 can be more reliably exerted. By making the content of the skeleton forming agent 14 in the total solid content of the negative electrode active material 13, the skeleton forming agent 14, the conductive auxiliary agent 15 and the binder 16 3.0% by mass or more, the function of the skeleton forming agent 14 can be more fully obtained. In addition, by making the content of the skeleton forming agent 14 40.0% by mass or less, the energy density can be further prevented from decreasing. The more preferred content of the skeleton forming agent 14 is 5.0 to 30.0% by mass.
[0063] Here, in the negative electrode 1 for a non-aqueous electrolyte secondary battery of the present embodiment, the skeleton forming agent 14 is disposed at least at the interface between the first negative electrode material 12 and the second negative electrode material 19 and the current collector 11 and in the pores of the current collector 11. More specifically, the skeleton forming agent 14 is disposed not only at the interface between the current collector 11 and the negative electrode material 12, but also uniformly disposed throughout the current collector 11 and the first negative electrode material 12, and dispersedly exists between the negative electrode active materials 13. In contrast, in the conventional negative electrode for a non-aqueous electrolyte secondary battery, the skeleton forming agent is biased toward the surface of the negative electrode material.
[0064] In addition, the negative electrode 1 for lithium ion secondary battery of the present embodiment contains a conductive auxiliary agent 15 in the first region 17. As the conductive auxiliary agent 15, there is no particular limitation as long as it has electronic conductivity, and metals, carbon materials, conductive polymers, conductive glass, etc. can be used. Specifically, acetylene black (AB), Ketjen black (KB), furnace black (FB), thermal black, lamp black, channel carbon black, drum carbon black, disc carbon black, carbon black (CB), carbon fiber (such as vapor grown carbon fiber VGCF (registered trademark)), carbon nanotubes (CNT), carbon nanohorns, graphite, graphene, glassy carbon, amorphous carbon, etc. can be cited, and one or more of them can be used.
[0065] When the total amount of the negative electrode active material 13, the conductive aid 15, and the binder 16 contained in the first negative electrode material 12 is 100 mass %, the content of the conductive aid 15 is preferably 0 to 20.0 mass %. If the content of the conductive aid 15 is within this range, the negative electrode capacity density will not be reduced and the conductivity can be improved, and a gap that can hold a sufficient amount of the skeleton forming agent 14 can be formed inside the first negative electrode material 12. A more preferred content of the conductive aid 15 is 8.8 to 25.0 mass %.
[0066] The bulk density of the conductive additive 15 of the present embodiment is preferably 0.04 to 0.25 mg / cm 3 By setting the volume density of the conductive auxiliary agent 15 within this range, the skeleton forming agent 14 can be fully impregnated, so that the effect of the skeleton forming agent 14 can be fully exerted. A more preferred volume density of the conductive auxiliary agent 15 is 0.04 to 0.15 mg / cm 3 .
[0067] The negative electrode 1 for lithium ion secondary battery of the present embodiment contains a binder 16 in the first region 17. As the binder 16, for example, polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), polyimide (PI), polyamide, polyamideimide, aromatic polyamide, polyacrylic acid, styrene-butadiene rubber (SBR), ethylene-vinyl acetate copolymer (EVA), styrene-ethylene-butylene-styrene copolymer (SEBS), carboxymethyl cellulose (CMC), xanthan gum, polyvinyl alcohol (PVA), ethylene-vinyl alcohol, polyvinyl butyral (PVB), ethylene-vinyl alcohol, polyethylene (PE), polypropylene (PP), polyacrylic acid, lithium polyacrylate, sodium polyacrylate, potassium polyacrylate, ammonium polyacrylate, methyl polyacrylate, ethyl polyacrylate, polyacrylamide, polyacrylate, epoxy resin, polyacrylate, etc. can be used alone. One of the organic materials such as polyethylene terephthalate (PET), polybutylene terephthalate (PBT), nylon, vinyl chloride, silicone rubber, nitrile rubber, cyanoacrylate, urea resin, melamine resin, phenol resin, latex, polyurethane, silylated urethane, nitrocellulose, dextrin, polyvinyl pyrrolidone, vinyl acetate, polystyrene, allyl chloride, resorcinol resin, polyaromatic resin, modified silicone, methacrylic resin, polybutene, butyl rubber, 2-propionic acid, cyanoacrylate, methyl methacrylate, glycidyl methacrylate, acrylic acid oligomer, 2-hydroxyethyl acrylate, alginic acid, starch, lacquer, sucrose, gelatin, casein, cellulose nanofibers, etc., or two or more thereof can be used in combination.
[0068] In addition, an adhesive obtained by mixing the above-mentioned various organic adhesives with an inorganic adhesive can also be used. Examples of the inorganic adhesive include silicate-based, phosphate-based, sol-based, cement-based, and the like. For example, lithium silicate, sodium silicate, potassium silicate, cesium silicate, guanidine silicate, ammonium silicate, fluorosilicate, borate, lithium aluminate, sodium aluminate, potassium aluminate, aluminum silicate, lithium aluminate, sodium aluminate, potassium aluminate, polyaluminum chloride, polyaluminum sulfate, polyaluminum sulfate silicate, aluminum sulfate, aluminum nitrate, ammonium alum, lithium alum, sodium alum, potassium alum, chrome alum, iron alum, manganese alum, nickel ammonium sulfate, diatomaceous earth, polyzirconoxane, polytantaloxane, mullite, white carbon black, silica sol, colloidal silica, fumed silica, alumina solution, etc. can be used alone. One of the inorganic materials such as colloid, colloidal alumina, fumed alumina, zirconia sol, colloidal zirconia, fumed zirconia, magnesia sol, colloidal magnesia, fumed magnesia, calcium oxide sol, colloidal calcium oxide, fumed calcium oxide, titanium dioxide sol, colloidal titanium dioxide, fumed titanium dioxide, zeolite, silicoaluminophosphate zeolite, sepiolite, montmorillonite, kaolin, saponite, aluminum phosphate, magnesium phosphate, calcium phosphate, iron phosphate, copper phosphate, zinc phosphate, titanium phosphate, manganese phosphate, barium phosphate, tin phosphate, low melting point glass, plaster, gypsum, magnesium cement, lead monoxide cement (lithargecement), Portland cement (Portland cement), blast furnace cement, fly ash cement, silicate cement (silicacement), phosphate cement, concrete, solid electrolyte, etc., or two or more thereof can be used in combination.
[0069] In addition, in the present embodiment, since the negative electrode active material 13 and the skeleton forming agent 14 are firmly bonded by using the above-mentioned interface layer formed by using the second negative electrode material 19 having the skeleton forming agent 14, all of the above-mentioned binder 16 can be used. When the total of the negative electrode active material 13, the conductive auxiliary agent 15, and the binder 16 contained in the first negative electrode material 12 is set to 100% by mass, the content of the binder 16 is preferably 0.1 to 60% by mass. By making the content of the binder 16 within this range, the negative electrode capacity density will not be reduced and the ion conductivity can be improved, and high mechanical strength is obtained, and more excellent cycle life characteristics are obtained. The more preferred content of the binder 16 is 0.5 to 30% by mass.
[0070] In the negative electrode 1 for a non-aqueous electrolyte secondary battery of the present embodiment, there are provided on the current collector 11: a pair of first regions 17 (hereinafter, also referred to as "first regions") formed on both outer sides in the thickness direction of the current collector 11 and arranged with the first negative electrode material 12 and the second negative electrode material 19; and a second region 18 (hereinafter, also referred to as "second region" or "central space layer") formed in the center in the thickness direction of the current collector and arranged with the second negative electrode material 19 without the first negative electrode material 12. With such a configuration, in the manufacturing step of the negative electrode 1 for a non-aqueous electrolyte secondary battery of the present embodiment in which the second negative electrode material 19 having the skeleton forming agent 14 is applied to the entire current collector 11, the skeleton forming agent 14 can penetrate from the second region 18 to the first region 17 in addition to penetrating from the first region 17 to the inside of the current collector 11. That is, the skeleton forming agent 14 fully penetrates into the entire inside of the current collector 11. By allowing the skeleton forming agent 14 to fully permeate the entire interior of the current collector 11 , structural degradation inside the negative electrode can be suppressed, and cycle durability can also be improved.
[0071] The thickness of the second region 18 formed at the center of the thickness direction of the current collector and having the second negative electrode material 19 but not the first negative electrode material 12 is preferably 0.5 to 15% of the thickness of the entire electrode. The thickness of the second region 18 is more preferably 5 to 100 μm.
[0072] The thickness of the negative electrode 1 for a non-aqueous electrolyte secondary battery of the present embodiment composed of the above-mentioned structure is preferably 50 μm to 1000 μm. If the thickness of the negative electrode 1 for a non-aqueous electrolyte secondary battery is within this range, the endurance degradation can be suppressed and the energy density can be improved compared with the past. The thickness of the negative electrode 1 for a non-aqueous electrolyte secondary battery is more preferably 150 μm to 800 μm.
[0073] In addition, in the negative electrode 1 for a non-aqueous electrolyte secondary battery of the present embodiment, the distance between the current collector 11 composed of a porous metal body and the negative electrode active material 13 is preferably 50 μm or less. If the distance between the current collector 11 composed of a porous metal body and the negative electrode active material 13 is 50 μm or less, the durable degradation can be suppressed. More preferably, the distance between the current collector 11 composed of a porous metal body and the negative electrode active material 13 is 30 μm or less.
[0074] [positive electrode]
[0075] Next, a positive electrode when a lithium ion secondary battery is constructed using the above-mentioned negative electrode will be described.
[0076] The positive electrode active material is not particularly limited as long as it is a positive electrode active material commonly used in lithium ion secondary batteries, for example, positive electrode active materials such as alkali metal transition metal oxides, vanadium, sulfur, solid solution systems (lithium excess systems, sodium excess systems, potassium excess systems), carbon systems, and organic systems are used.
[0077] The positive electrode for lithium ion secondary battery of this embodiment may also contain a skeleton forming agent like the negative electrode. As the skeleton forming agent, the same skeleton forming agent as that of the negative electrode can be used, and the preferred content of the skeleton forming agent is also the same as that of the negative electrode.
[0078] The positive electrode for lithium ion secondary battery of this embodiment may also contain a conductive auxiliary agent. As the conductive auxiliary agent, the above-mentioned various conductive auxiliary agents that can be used in the negative electrode are used. The preferred content of the conductive auxiliary agent is also the same as that of the negative electrode.
[0079] The positive electrode for lithium ion secondary battery of the present embodiment may also contain a binder. As a binder, for example, one of organic materials such as polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), hexafluoropropylene, tetrafluoroethylene, polyacrylic resin, alginic acid, etc. can be used alone, or two or more can be used in combination. In addition, it can also be a binder mixed with these organic binders and inorganic binders. For example, inorganic binders can include silicate systems, phosphate systems, sol systems, cement systems, etc.
[0080] As the current collector used in the positive electrode, as long as it is a material with electronic conductivity and capable of energizing the positive electrode active material maintained, there is no particular limitation. For example, conductive materials such as C, Ti, Cr, Ni, Cu, Mo, Ru, Rh, Ta, W, Os, Ir, Pt, Au, Al, and alloys containing two or more of these conductive materials (for example, stainless steel or Al-Fe alloy) can be used. When using materials other than the above-mentioned conductive materials, for example, it can be a multilayer structure of different metals such as Al coated on iron or different elements such as C coated on Al. From the viewpoint of high conductivity and high stability in the electrolyte, the current collector is preferably C, Ti, Cr, Au, Al, stainless steel, etc., and further from the viewpoint of oxidation resistance and material cost, it is preferably C, Al, stainless steel, etc. More preferably, Al or Al alloy coated with carbon, stainless steel coated with carbon.
[0081] In addition, the shape of the current collector used in the positive electrode is linear, rod-shaped, plate-shaped, foil-shaped, porous, wherein, in terms of increasing the packing density and the skeleton forming agent being easily infiltrated into the active material layer, it can be porous. Regarding the porous shape, it can be cited: a mesh, a woven fabric, a non-woven fabric, an embossed body, a punched body, an expanded body, or a foamed body. The same porous metal body as the negative electrode can also be used.
[0082] [Diaphragm]
[0083] In the lithium ion secondary battery of the present embodiment, a separator commonly used in lithium ion secondary batteries can be used as the separator. For example, a polyethylene microporous membrane, a polypropylene microporous membrane, a glass nonwoven fabric or an aromatic polyamide nonwoven fabric, a polyimide microporous membrane, a polyolefin microporous membrane, etc. can be used as the separator.
[0084] [Electrolytes]
[0085] In the lithium ion secondary battery of the present embodiment, an electrolyte commonly used in lithium ion secondary batteries can be used as an electrolyte. For example, an electrolyte solution, a gel electrolyte, a solid electrolyte, an ionic liquid, and a molten salt in which an electrolyte is dissolved in a solvent can be cited. Here, the electrolyte solution refers to an electrolyte solution in a state where an electrolyte is dissolved in a solvent.
[0086] As the electrolyte of a lithium ion secondary battery, it is necessary to contain lithium ions as the carrier responsible for conduction. Therefore, as the electrolyte salt of a lithium ion secondary battery, there is no particular limitation as long as it is an electrolyte salt that can be used in a lithium ion secondary battery, and lithium salt is preferred. As the lithium salt, at least one selected from the following groups can be used, or two or more can be used in combination, and the group includes lithium hexafluorophosphate (LiPF 6 ), lithium perchlorate (LiClO 4 ), lithium tetrafluoroborate (LiBF 4 ), lithium trifluoromethanesulfonate (LiCF 3 SO 4 ), lithium bis(trifluoromethanesulfonyl)imide (LiN(SO 2 CF 3 ) 2 ), lithium bis(pentafluoroethanesulfonyl)imide (LiN(SO 2 C 2 F 5 ) 2 ), lithium bis(oxalatoborate) (LiBC 4 O 8 )wait.
[0087] The solvent for the electrolyte is not particularly limited as long as it is a solvent for the electrolyte that can be used in a lithium ion secondary battery. For example, at least one selected from the following group can be used, or two or more can be used in combination. The group includes: propylene carbonate (PC), ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), γ-butyrolactone (GBL), methyl-γ-butyrolactone, dimethoxymethane (DMM), dimethoxyethane (DME), vinylene carbonate (VC), vinyl ethylene carbonate (EVC), fluoroethylene carbonate (FEC), and vinyl sulfite (ES).
[0088] The concentration of the electrolyte solution (the concentration of the salt in the solvent) is not particularly limited, but is preferably 0.1 to 3.0 mol / L, and more preferably 0.8 to 2.0 mol / L.
[0089] Ionic liquids or molten salts are classified into pyridine series, alicyclic amine series, aliphatic amine series, etc. according to the type of cation (positive ion). By selecting the type of anion (negative ion) combined with them, a variety of ionic liquids or molten salts can be synthesized. Among the cations, there are ammonium series, phosphonium series ions, inorganic series ions, etc. such as imidazolium salts and pyridinium salts, and as examples of anions, there are halogen series such as bromide ions and trifluoromethanesulfonates, boron series such as tetraphenylborate, phosphorus series such as hexafluorophosphate, etc.
[0090] Ionic liquids or molten salts can be obtained by the following known synthesis methods, for example, by reacting cations such as imidazolinium with Br - , Cl - , BF 4- PF 6- ,(CF 3 SO 2 ) 2 N - CF 3 SO 3- 、FeCl 4- If it is an ionic liquid or molten salt, it can function as an electrolyte even without adding an electrolyte.
[0091] Solid electrolytes are classified into sulfide-based, oxide-based, hydride-based, organic polymer-based, etc. Most of them are amorphous or crystalline, consisting of salts and inorganic derivatives that can become carriers. Because it is not necessary to use a flammable aprotic organic solvent like an electrolyte, it is not easy to cause ignition or leakage of gas or liquid, and it can be expected to become a secondary battery with excellent safety.
[0092] [Manufacturing method]
[0093] Next, a method for manufacturing the lithium ion secondary battery of this embodiment will be described.
[0094] The manufacturing method of the negative electrode for lithium-ion secondary battery of the present embodiment has a first step, and the first step is to provide a pair of first regions formed on the two outer sides of the collector in the thickness direction and arranged with the first negative electrode material and the second negative electrode material, and a second region formed in the center of the thickness direction of the collector and arranged with the second negative electrode material but not arranged with the first negative electrode material, and then apply the negative electrode material containing the first negative electrode material containing the negative electrode active material, the conductive aid and the adhesive only on the first region and dry it, thereby forming the following negative electrode layer precursor, which has a pair of first regions formed on the two outer sides of the collector in the thickness direction and arranged with the first negative electrode material, and a second region formed in the center of the thickness direction of the collector and not arranged with the first negative electrode material. Figure 3 This is an illustration of the first step.
[0095] As a first step, for example, on the one hand, a nickel porous body is prepared, which is prepared by manufacturing a nickel porous material with a thickness of 1000 μm and pre-rolling it into a roll, and on the other hand, a negative electrode active material, a binder, a conductive aid, etc. are mixed with N-methyl-2-pyrrolidone to prepare a paste-like slurry of a negative electrode material containing a first negative electrode material as a negative electrode material containing a first negative electrode material. From the perspective of the coating and filling properties of the porous material, the viscosity of the prepared negative electrode material slurry containing the first negative electrode material is preferably 5,000 to 30,000 mPa·s. Then, the slurry-like negative electrode material is filled and coated on the inside of the nickel porous body using a coater 21 and dried, and then a pressure adjustment treatment is performed to obtain a negative electrode layer precursor.
[0096] In addition, the negative electrode layer precursor may be kept wet instead of being dried as described above. In addition, in addition to the above-mentioned slurry coating, for example, the following methods may be cited: using chemical plating or sputtering, evaporation, gas deposition, impregnation, etc., so that the negative electrode active material (precursor) forms a negative electrode active material layer inside the porous collector and integrates. Among them, from the perspective of the lyophilicity of the skeleton forming agent and the cost of electrode manufacturing, the slurry filling coating method or the impregnation method is preferred.
[0097] In addition, the manufacturing method of the negative electrode for lithium ion secondary battery of the present embodiment has a second step, which is to harden the skeleton forming agent and form the skeleton of the negative electrode active material layer by impregnating the solution 22 containing the second negative electrode material having a skeleton forming agent into the negative electrode layer precursor formed in the first step and drying it. The skeleton forming agent includes a silicate having a siloxane bond or a phosphate having a phosphate bond. For example, the silicate having a siloxane bond or the phosphate having a phosphate bond is purified by a dry or wet method and adjusted by adding water to prepare a solution of the negative electrode material (skeleton forming agent liquid) containing the second negative electrode material containing the skeleton forming agent. At this time, a surfactant can also be mixed. As a method using a dry method, for example, SiO is added to water in which an alkali metal hydroxide is dissolved. 2 , and then treated in an autoclave at 150°C to 250°C to produce an alkali metal silicate. As a wet method, for example, an alkali metal carbonate compound and SiO2 are reacted at 1000°C to 2000°C. 2 The resulting mixture is calcined and dissolved in hot water. Figure 4 This is an illustration of the second step.
[0098] Next, a skeleton forming agent liquid is applied to the surface of the negative electrode layer precursor to coat the negative electrode active material. In addition to the method of immersing the negative electrode layer precursor in a tank storing a skeleton forming agent liquid, the skeleton forming agent can also be applied by dripping and applying the skeleton forming agent to the surface of the negative electrode layer precursor, spraying, screen printing, curtain coating, spin coating, gravure coating, die nozzle coating, etc. The skeleton forming agent applied to the surface of the negative electrode layer precursor will penetrate into the negative electrode and enter the gaps between the negative electrode active material and the first conductive aid. Then, the skeleton forming agent is dried by heat treatment to harden it. In this way, the skeleton forming agent forms the skeleton of the negative electrode active material layer.
[0099] The preferred coating method of the skeleton forming agent of the present embodiment to the negative electrode layer precursor is as follows: the entire negative electrode layer precursor is impregnated with the skeleton forming agent liquid, and the entire second region is impregnated with the skeleton forming agent liquid. It is speculated that the capillary phenomenon is generated by immersion in the groove of the skeleton forming agent liquid, and the skeleton forming agent becomes easier to penetrate from the second region to the first region. The more preferred coating method is as follows: when the entire negative electrode layer precursor is impregnated with the skeleton forming agent liquid, the skeleton forming agent liquid is impregnated from the surface with the smallest cross-sectional area in the second region. It is speculated that the reason is that the effect of the capillary phenomenon will be maximized.
[0100] In addition, it is preferred that the skeleton-forming agent liquid adhering to the surface of the negative electrode layer precursor after impregnation is removed as excess.
[0101] Regarding the above-mentioned heat treatment, if the temperature is high, the heat treatment time can be shortened, and the strength of the skeleton forming agent is improved. It is preferably 80°C or more, more preferably 100°C or more, and ideally 110°C or more. In addition, as the upper limit temperature of the heat treatment, there is no particular limitation as long as the collector is not melted, for example, it can be increased to the melting point of copper, that is, about 1000°C. If it is a conventional electrode, because there is a situation of carbonization of the binder or softening of the collector, the upper limit temperature is also estimated to be much lower than 1000°C. In this embodiment, by using a skeleton forming agent, the skeleton forming agent will show excellent heat resistance and be stronger than the strength of the collector, so the upper limit of the temperature is 1000°C.
[0102] The heat treatment time can be 0.5 to 100 hours. The heat treatment environment may be in the air, but it is preferably carried out in a non-oxidizing environment to prevent oxidation of the current collector.
[0103] Here, in the method for producing a negative electrode for a lithium ion secondary battery of the present embodiment, the ratio of the density B of the negative electrode layer formed in the second step to the density A of the negative electrode layer precursor formed in the first step, that is, B / A, is 0.9.
[0104] In the method for producing a negative electrode for a lithium ion secondary battery of the present embodiment, the density A of the negative electrode layer precursor formed in the first step is set to 0.5 to 2.0 g / cm 3 In this way, the ratio B / A (i.e., density increase ratio) of the density B of the negative electrode layer to the density A of the negative electrode layer precursor can be more reliably made within the above range, thereby enhancing the effect of the above skeleton forming agent. The more preferred range of the density A of the negative electrode layer precursor is 0.6 to 1.5 g / cm 3 By making the density A of the negative electrode layer precursor 0.6 g / cm 3 The above can suppress the decrease in energy density caused by the decrease in electrode density. By making it 1.5 g / cm 3 Below, the capacity reduction can be suppressed.
[0105] The positive electrode for lithium ion secondary battery of the present invention includes a step of manufacturing a positive electrode by applying a positive electrode material including a positive electrode active material, a conductive aid and a binder to a collector, drying it and rolling it. For example, on the one hand, an aluminum foil is prepared, which is made by manufacturing a rolled aluminum foil with a thickness of 10 μm and pre-rolling it into a roll shape, and on the other hand, a paste slurry is prepared by mixing a positive electrode active material, a binder, a conductive aid, etc. as a positive electrode material. Then, the slurry-like positive electrode material is applied to the surface of aluminum and dried, and then a rolling step is performed to obtain a positive electrode. In addition, a foamed porous body composed of a metal can also be used as a collector. It is characterized in that the collector is filled with an electrode composite. The method of filling the electrode composite in the collector is not particularly limited, and for example, the following method can be cited: by a press-in method, pressure is applied to fill the slurry containing the electrode composite into the interior of the mesh structure of the collector. After the electrode composite is filled, the filled current collector is dried and then pressurized to increase the density of the electrode composite, thereby adjusting the density to a desired value.
[0106] Finally, the obtained negative electrode and positive electrode are cut into required sizes, joined via a separator, and sealed while immersed in an electrolyte, thereby obtaining a lithium-ion secondary battery. As the structure of the lithium-ion secondary battery, it can be applied to existing battery forms or structures such as stacked batteries or wound batteries.
[0107] [Effect]
[0108] According to this embodiment, the following effects can be achieved.
[0109] The present embodiment constitutes the following negative electrode for a non-aqueous electrolyte secondary battery, which comprises: a collector 11, which is composed of a porous metal body; a negative electrode active material 13, which is arranged in the pores of the porous metal body and is composed of a silicon-based material; a first negative electrode material 12, which has a conductive aid 15 and a binder 16; and a second negative electrode material 19, which is arranged in the pores of the porous metal body and has a skeleton former 14, and the skeleton former 14 contains a silicate with a siloxane bond; and the above-mentioned negative electrode for a non-aqueous electrolyte secondary battery has: a pair of first regions 17, which are formed on both outer sides of the collector 11 in the thickness direction and are arranged with the first negative electrode material and the second negative electrode material; and a second region 18, which is formed in the center of the collector in the thickness direction and is arranged with the second negative electrode material instead of the first negative electrode material.
[0110] First, by using a porous metal body as the current collector 11, the first negative electrode material 12 can be fixed in a micrometer-order region by utilizing the porous metal skeleton, thereby suppressing the peeling and cracking of the negative electrode.
[0111] Furthermore, by using the second negative electrode material 19 having the skeleton forming agent 14, the first negative electrode material 12 can be fixed in the nanoscale region. More specifically, by forming a third phase composed of the skeleton forming agent 14 at the interface between the current collector 11 composed of a porous metal body and the negative electrode active material 13, the negative electrode active material 13 is firmly bonded in the first negative electrode material 12, thereby suppressing the shedding during expansion and contraction, thereby suppressing the structural degradation of the electrode.
[0112] In addition, the current collector 11 has: a pair of first regions 17, which are formed on both outer sides of the current collector in the thickness direction and are configured with the first negative electrode material and the second negative electrode material; and a second region 18, which is configured with the second negative electrode material but not the first negative electrode material. Thereby, the second negative electrode material 19 having the skeleton forming agent 14 not only penetrates from the first region 17 to the interior of the current collector 11, but also penetrates from the second region 18 to the first region 17. In other words, the second negative electrode material 19 having the skeleton forming agent 14 can fully penetrate into the entire interior of the current collector 11, so that the structural degradation of the negative electrode is suppressed, and the cycle durability can be improved.
[0113] Therefore, by having the first region 17 and the second region 18 in the current collector 11, the second negative electrode material 19 having the skeleton forming agent 14 can fully penetrate into the entire interior of the negative electrode, so even if the negative electrode uses the negative electrode active material 13 composed of a silicon-based material with a high capacity and a large expansion and contraction rate, the negative electrode structure can be maintained when the SOC (State of Charge) is 0 to 100. In addition, the structural degradation of the negative electrode due to the high capacity and high unit area weight caused by the thick film of the negative electrode, the disconnection of the conductive path, etc. can be suppressed, so high cycle durability can also be achieved.
[0114] <Second embodiment>
[0115] In addition, as another embodiment of the negative electrode for a non-aqueous electrolyte secondary battery of the present invention, the following embodiment (hereinafter also referred to as the second embodiment) is also described with reference to the attached drawings. Figure 1While explaining in detail, it comprises: a collector, which is composed of a porous metal body; a first negative electrode material, which is arranged in the pores of the porous metal body and has a conductive aid; a second negative electrode material, which is arranged in the pores of the porous metal body and has a negative electrode active material composed of a silicon-based material, a conductive aid and a binder; and a third negative electrode material, which is arranged in the pores of the porous metal body and has a skeleton former, and the skeleton former contains a silicate with a siloxane bond; and the negative electrode for the non-aqueous electrolyte secondary battery comprises: a pair of first regions, which are formed on both outer sides of the collector in the thickness direction and are arranged with the first negative electrode material, the second negative electrode material and the third negative electrode material; and a second region, which is formed in the center of the collector in the thickness direction and is arranged with the first negative electrode material and the third negative electrode material but not the second negative electrode material.
[0116] [negative electrode]
[0117] like Figure 2 As shown, the negative electrode 1a for the non-aqueous electrolyte secondary battery of this embodiment comprises: a collector 11, which is composed of a porous metal body; a first negative electrode material 12a, which is arranged in the pores of the porous metal body and has a conductive aid 15; a second negative electrode material 19a, which is arranged in the pores of the porous metal body and has a negative electrode active material 13 composed of a silicon-based material, a conductive aid 15 and a binder 16; and a third negative electrode material 20, which is arranged in the pores of the porous metal body and has a skeleton former 14, and the skeleton former 14 contains a silicate having a siloxane bond.
[0118] The negative electrode 1a for the non-aqueous electrolyte secondary battery of this embodiment has on the collector 11: a pair of first regions 17a, formed on the two outer sides in the thickness direction of the collector 11 and arranged with a first negative electrode material 12a, a second negative electrode material 19a and a third negative electrode material 20; and a second region 18a, formed in the center in the thickness direction of the collector and arranged with the first negative electrode material 12a and the third negative electrode material 20 without the second negative electrode material 19a.
[0119] For example, by applying the present embodiment to a negative electrode for a lithium ion secondary battery, a negative electrode for a lithium ion secondary battery and a lithium ion secondary battery having the negative electrode can be provided, which can better suppress the structural degradation of the electrode by further improving the permeability of the skeleton forming agent into the collector body composed of a porous metal body, and can also further improve the cycle durability. Below, an example of applying the present embodiment to a negative electrode for a lithium ion secondary battery is described in detail, and various additions, changes or deletions can be made within the scope of the subject matter of the present invention.
[0120] In the negative electrode 1a for a non-aqueous electrolyte secondary battery of the present embodiment, the current collector 11 has: a pair of first regions 17a (hereinafter, also referred to as "first regions") formed on both outer sides of the current collector 11 in the thickness direction and arranged with the first negative electrode material 12a, the second negative electrode material 19a and the third negative electrode material 20; and a second region 18a (hereinafter, also referred to as "second region" or "central space layer") formed in the center of the current collector in the thickness direction and arranged with the first negative electrode material 12a and the third negative electrode material 20 without the second negative electrode material 19a. By setting such a configuration, in the manufacturing step of the negative electrode 1a for a non-aqueous electrolyte secondary battery of the present embodiment in which the third negative electrode material 20 having the skeleton forming agent 14 is applied to the entire current collector 11, the skeleton forming agent 14 can penetrate from the second region 18a to the first region 17a in addition to penetrating from the first region 17a to the inside of the current collector 11. That is, the skeleton forming agent 14 fully penetrates into the entire inside of the current collector 11. By allowing the skeleton forming agent 14 to fully penetrate the entire interior of the current collector 11 , structural degradation inside the negative electrode can be further suppressed, and cycle durability can also be further improved.
[0121] The thickness of the second region 18a formed at the center of the thickness direction of the current collector and where the first negative electrode material 12a and the third negative electrode material 20 are arranged but the second negative electrode material 19a is not arranged is preferably 0.5 to 15% of the thickness of the entire electrode. The thickness of the second region 18a is more preferably 5 to 100 μm.
[0122] In the present embodiment, it is preferred that the first negative electrode material 12 a including the conductive auxiliary agent 15 is provided in the first region 17 a and the second region 18 a of the current collector 11 .
[0123] As the conductive aid 15 included in the first negative electrode material 12a in this embodiment, the conductive aid 15 in the first embodiment and a fibrous carbon material or a material having a DBP (dibutyl phthalate) oil absorption of 200 ml / g or more as specified in JIS K 6217-4 can be preferably used. The conductive aid 15 having the above-mentioned properties is a porous body with a high specific surface area and high liquid absorption. When the collector (negative electrode layer precursor) containing such a conductive aid 15 is coated with the third negative electrode material 20 having the skeleton forming agent 14, the third negative electrode material 20 having the skeleton forming agent 14 shows a higher liquid absorption than when the collector (negative electrode layer precursor) in the first embodiment is coated with the second negative electrode material having the skeleton forming agent 14. This is presumably because the inclusion of the conductive auxiliary agent 15 in the current collector causes a stronger capillary phenomenon, thereby further improving the dispersibility and permeability of the third negative electrode material 20 having the skeleton forming agent 14 into the entire interior of the current collector 11 .
[0124] As specific examples of the conductive aid 15 that may be contained in the first negative electrode material of the present embodiment, there can be cited acetylene black (AB), Ketjen black (KB), furnace black (FB), thermal black, lamp black, channel black, drum black, disc black, carbon black (CB), carbon fiber (for example, vapor grown carbon fiber VGCF (registered trademark)), carbon nanotubes (CNT), carbon nanohorns, graphite, graphene, glassy carbon, amorphous carbon, etc., and one or more of them can be used.
[0125] The weight per unit area of the conductive auxiliary agent 15 contained in the first negative electrode material is preferably 0.1 to 1.0 mg / cm 2 By setting the content of the conductive auxiliary agent 15 contained in the first negative electrode material to be within this range, the effect of the conductive auxiliary agent 15 can be more reliably exerted.
[0126] In addition, when the total amount of the negative electrode active material 13, the conductive aid 15, and the binder 16 contained in the first negative electrode material 12a and the second negative electrode material 19a is set to 100% by mass, the content of the conductive aid 15 when the first negative electrode material 12a and the second negative electrode material 19a are combined is preferably 0 to 20.0% by mass. If the total content of the conductive aid 15 is within this range, the negative electrode capacity density will not be reduced and the conductivity can be improved, and a gap that can hold enough skeleton forming agent 14 can be formed inside the collector 11, and the permeability of the skeleton forming agent into the collector can be improved by capillary phenomenon.
[0127] The bulk density of the conductive additive 15 of the present embodiment is preferably 0.04 to 0.25 mg / cm 3 By making the volume density of the conductive aid 15 within this range, the third negative electrode material 20 having the skeleton forming agent 14 can be fully impregnated into the collector 11 by the capillary phenomenon, so that the effect of the skeleton forming agent 14 can be fully exerted. The more preferred volume density of the conductive aid 15 is 0.04 to 0.15 mg / cm 3 .
[0128] The content (density) of the skeleton forming agent 14 relative to the total of the first negative electrode material 12a, the second negative electrode material 19a, and the third negative electrode material 20 is preferably 0.5 to 2.0 mg / cm 2 When the content of the skeleton forming agent 14 relative to the total of the first negative electrode material 12a, the second negative electrode material 19a, and the third negative electrode material 20 is within this range, the effect of using the skeleton forming agent 14 can be more reliably exerted.
[0129] When the solid content of the negative electrode active material 13, the skeleton former 14, the conductive aid 15 and the binder 16 contained in the first negative electrode material 12a, the second negative electrode material 19a and the third negative electrode material 20 is set to 100% by mass, the content of the skeleton former 14 is preferably 3.0 to 40.0% by mass. If the content of the skeleton former 14 is within this range, the effect of using the above-mentioned skeleton former 14 can be more reliably exerted. By making the content of the skeleton former 14 in the negative electrode material 12 3.0% by mass or more, the function of the skeleton former 14 can be more fully obtained. Moreover, by making the content of the skeleton former 14 40.0% by mass or less, the energy density can be further prevented from decreasing. The more preferred content of the skeleton former 14 is 5.0 to 30.0% by mass.
[0130] In this embodiment, since the negative electrode active material 13 and the skeleton forming agent 14 are firmly bonded by using the above-mentioned interface layer formed by using the third negative electrode material 20 having the skeleton forming agent 14, all the binders 16 of the first embodiment can be used. When the total of the negative electrode active material 13, the conductive aid 15, and the binder 16 contained in the first negative electrode material 12a and the second negative electrode material 19a is set to 100% by mass, the content of the binder 16 is preferably 0.1 to 60% by mass. By making the content of the binder 16 within this range, the negative electrode capacity density will not be reduced and the ion conductivity can be improved, and high mechanical strength is obtained, and more excellent cycle life characteristics are obtained. The more preferred content of the binder 16 is 0.5 to 30% by mass.
[0131] [Manufacturing method]
[0132] Next, a method for manufacturing the lithium ion secondary battery of this embodiment will be described.
[0133] The method for producing a negative electrode for a lithium ion secondary battery of the present embodiment includes a first step of applying a conductive agent solution containing a first negative electrode material having a conductive auxiliary agent to a current collector and drying the solution to form a conductive path in the current collector.
[0134] For example, on the one hand, a nickel porous body is prepared, which is a nickel porous material with a thickness of 1000 μm and pre-rolled into a roll, and on the other hand, a conductive agent is dissolved or dispersed in N-methyl-2-pyrrolidone to prepare a conductive agent solution containing a first negative electrode material. Then, the conductive agent solution containing the first negative electrode material is filled and coated on the inside of the nickel porous body and dried, and then a voltage adjustment treatment is performed to obtain a negative electrode layer precursor. In addition, the negative electrode layer precursor may not be dried as described above but kept wet. In addition, in addition to the above-mentioned slurry coating, the coating method of the conductive agent solution containing the first negative electrode material having a conductive agent can also utilize a method of dripping and coating the conductive agent solution on the surface of the collector, a spraying method, a screen printing method, a curtain coating method, a spin coating method, a gravure coating method, a die nozzle coating method, etc. Among them, from the perspective of electrode manufacturing cost, a slurry filling coating method or an immersion method is preferred.
[0135] Moreover, the manufacturing method of the negative electrode for lithium-ion secondary battery of this embodiment has a second step, and the second step is to form the following negative electrode layer precursor on the negative electrode layer precursor formed in the first step in the same way as the first step of the first embodiment, wherein the negative electrode layer precursor has a pair of first regions and second regions on the collector, the first regions are formed on both outer sides in the thickness direction of the collector and are arranged with the first negative electrode material and the second negative electrode material, and the second region is formed in the center in the thickness direction of the collector and is arranged with the first negative electrode material but not the second negative electrode material. Figure 5 It is a schematic diagram of the first step and the second step of this embodiment.
[0136] As the second step of the manufacturing method of this embodiment, the first step of the first embodiment can be appropriately used within the scope of not hindering this embodiment. Moreover, for the parts not described in detail, the structure and method of the first embodiment can also be appropriately used within the scope of not hindering this embodiment.
[0137] The manufacturing method of the negative electrode for lithium-ion secondary battery of this embodiment has a third step, and the third step is to impregnate the negative electrode layer precursor formed in the second step with a solution 22a containing a negative electrode material containing a third negative electrode material in the same way as the second step of the first embodiment and dry it, thereby hardening the skeleton former and forming the skeleton of the negative electrode active material layer, and the third negative electrode material has a skeleton former. Figure 6 It is a schematic diagram of the third step of this embodiment.
[0138] As the third step of the manufacturing method of the present embodiment, the second step of the first embodiment can be suitably used within the scope of not hindering the present embodiment. Moreover, with respect to the undescribed part, the structure and method of the first embodiment can also be suitably used within the scope of not hindering the present embodiment. The same is true for the preferred coating method of the skeleton forming agent.
[0139] In this embodiment, the nonaqueous electrolyte secondary battery having the nonaqueous electrolyte secondary battery negative electrode of this embodiment can be manufactured by using the nonaqueous electrolyte secondary battery negative electrode of this embodiment and the nonaqueous electrolyte secondary battery positive electrode produced in the first embodiment.
[0140] [Effect]
[0141] According to this embodiment, the following effects can be achieved.
[0142] In the present embodiment, the structure is composed of: a collector, which is composed of a porous metal body; a first negative electrode material, which is arranged in the pores of the porous metal body and has a conductive aid; a second negative electrode material, which is arranged in the pores of the porous metal body and has a negative electrode active material composed of a silicon-based material, a conductive aid and a binder; and a third negative electrode material, which is arranged in the pores of the porous metal body and has a skeleton former, and the skeleton former includes a silicate with a siloxane bond; and the present embodiment has: a pair of first regions, which are formed on both outer sides of the collector in the thickness direction and are arranged with the first negative electrode material, the second negative electrode material and the third negative electrode material; and a second region, which is formed in the center of the collector in the thickness direction and is arranged with the first negative electrode material and the third negative electrode material but not the second negative electrode material.
[0143] In this embodiment, by including the first negative electrode material having the conductive auxiliary agent 15 in a pair of first and second regions provided in the current collector 11, the skeleton forming agent 14 can be better penetrated into the first region 17 from the second region 18 by using the capillary phenomenon on the basis of penetrating into the first region 17. The first region is formed on both outer sides in the thickness direction of the current collector and is configured with the first negative electrode material, the second negative electrode material and the third negative electrode material, and the second region is formed in the center in the thickness direction of the current collector and is configured with the first negative electrode material and the third negative electrode material 20 without configuring the second negative electrode material. In other words, the skeleton forming agent 14 can better fully penetrate into the entire interior of the current collector 11, so that the structural degradation of the negative electrode is better suppressed, and the improvement of the cycle durability can also be better achieved.
[0144] Therefore, by setting the structure of the second embodiment, in addition to the skeleton forming agent 14 penetrating into the first region 17, the skeleton forming agent 14 can also better penetrate from the second region 18 to the first region 17 by using a capillary phenomenon. Therefore, even if the negative electrode active material 13 composed of a silicon-based material with a high capacity and a large expansion and contraction rate is used, the negative electrode structure can be better maintained when a full charge and discharge cycle with an SOC of 0 to 100 is implemented. In addition, the structural degradation of the negative electrode caused by the high capacity brought about by the thick film of the negative electrode and the shedding at a high unit area weight, the disconnection of the conductive path, etc. can be better suppressed, so that high cycle durability can also be better achieved.
[0145] In addition, the present invention is not limited to the above-mentioned embodiments, and deformation and improvement within the scope of the purpose of the present invention are included in the present invention. For example, a non-aqueous electrolyte secondary battery is a secondary battery (electricity storage device) in which an electrolyte uses a non-aqueous electrolyte such as an organic solvent, and in addition to a lithium ion secondary battery, it also includes a sodium ion secondary battery, a potassium ion secondary battery, a magnesium ion secondary battery, a calcium ion secondary battery, etc. In addition, a lithium ion secondary battery refers to a secondary battery with a non-aqueous electrolyte that is not mainly composed of water and is a battery containing lithium ions as carriers responsible for conduction. For example, there are lithium ion secondary batteries, metal lithium batteries, lithium polymer batteries, all-solid-state lithium batteries, air lithium ion batteries, etc. In addition, other secondary batteries are also the same. Here, a non-aqueous electrolyte that is not mainly composed of water refers to an electrolyte whose main component is not water. That is, a known electrolyte used in a non-aqueous electrolyte secondary battery. Even if the electrolyte contains a little water, it can function as a secondary battery, but because it will have an adverse effect on the cycle characteristics, storage characteristics, and input-output characteristics of the secondary battery, it is ideal to have an electrolyte that is as free of water as possible. In reality, the water in the electrolyte is preferably less than 5000ppm.
[0146] [Example]
[0147] Next, examples of the present invention will be described, but the present invention is not limited to these examples.
[0148] <Example 1>
[0149] [Production of negative electrode]
[0150] A slurry of a negative electrode material containing a first negative electrode material is prepared, wherein the first negative electrode material contains silicon (particle size 1 to 3 μm) as a negative electrode active material, a conductive aid as shown in Table 1, and polyvinylidene fluoride (PVdF) as a binder. Then, the prepared slurry is filled in a pair of first regions formed on both outer sides of the thickness direction of the current collector of "Nickel-Celmet" (registered trademark) manufactured by Sumitomo Electric Industries, Ltd. as a current collector. At this time, a second region with a width of 50 μm is provided in the central part of the current collector. Afterwards, drying and voltage adjustment treatment are performed to obtain the following negative electrode layer precursor, which has a pair of first regions formed on both outer sides of the thickness direction of the current collector and configured with the first negative electrode material, and a second region formed in the center of the thickness direction of the current collector and not configured with the first negative electrode material.
[0151] On the other hand, the preparation of Na 2 O·3SiO 2 A 10% by mass aqueous solution is used as a skeleton forming agent liquid containing a second negative electrode material containing a skeleton forming agent and water. The negative electrode layer precursor obtained in the above is immersed in the prepared skeleton forming agent liquid. Then, after the immersion, the precursor of the negative electrode is heated and dried at 160°C, thereby obtaining the negative electrode of Example 1 as a negative electrode layer, which has a pair of first regions formed on both outer sides in the thickness direction of the collector and arranged with the first negative electrode material and the second negative electrode material, and a second region formed in the center in the thickness direction of the collector and arranged with the second negative electrode material but not the first negative electrode material.
[0152] [Production of positive electrode]
[0153] Preparation of LiNi 0.5 Co 0.2 Mn 0.3 O 2 (particle size 5 to 15 μm) as the positive electrode active material. Mix 94% by mass of the positive electrode active material, 4% by mass of carbon black as a conductive aid, and 2% by mass of polyvinylidene fluoride (PVdF) as a binder, and disperse the obtained mixture in an appropriate amount of N-methyl-2-pyrrolidone (NMP) to prepare a positive electrode composite slurry. Prepare a slurry with a thickness of 1.0 mm, a porosity of 95%, a pore number of 46 to 50 cells / inch, a pore diameter of 0.5 mm, and a specific surface area of 5000 m 2 / m 3 The foamed aluminum was used as the current collector. The coating amount was 90 mg / cm by the press-in method. 2 The prepared positive electrode composite slurry was applied to the current collector in a manner of , dried at 120° C. for 12 hours in a vacuum, and then roll-pressed at a pressure of 15 tons to prepare a positive electrode for a lithium ion secondary battery in which the pores of the foamed aluminum were filled with the electrode composite.
[0154] [Manufacturing of lithium-ion secondary batteries]
[0155] A microporous film of a three-layer laminate of polypropylene / polyethylene / polypropylene with a thickness of 25 μm was prepared as a separator and punched into a size of 100 mm in length and 90 mm in width. The positive electrode for lithium ion secondary battery and the negative electrode for lithium ion secondary battery obtained above were stacked in the order of positive electrode / separator / negative electrode / separator / positive electrode / negative electrode to prepare an electrode laminate.
[0156] Then, the electrode tabs were welded to the current collecting regions of the electrodes by ultrasonic welding. The electrode stack with the electrode tabs welded to it was inserted into a bag-shaped object made by heat-sealing aluminum laminate for secondary batteries to produce a laminated battery. 6 A solution prepared by dissolving ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a solvent mixed at a volume ratio of 3:4:3 was injected as an electrolyte into the laminated battery to prepare a lithium ion secondary battery.
[0157] <Example 2>
[0158] A slurry containing furnace black is prepared as a conductive solution containing a first negative electrode material having a conductive auxiliary agent, and is filled in the entire "Nickel-Celmet" (registered trademark) manufactured by Sumitomo Electric Industries, Ltd. as a current collector and dried, and then a voltage adjustment treatment is performed. Then, a slurry of a negative electrode material containing a second negative electrode material is prepared in the same manner as in Example 1, and is filled in a pair of first regions formed on both outer sides of the thickness direction of the current collector of "Nickel-Celmet" (registered trademark) manufactured by Sumitomo Electric Industries, Ltd. as a current collector, and the second negative electrode material contains silicon (particle size 1 to 3 μm) as a negative electrode active material, a conductive auxiliary agent shown in Table 1, and polyvinylidene fluoride (PVdF) as a binder. At this time, a second region with a width of 50 μm is provided in the central part of the current collector. Afterwards, drying and pressure adjustment treatment are carried out to obtain the following negative electrode layer precursor, which has a pair of first regions formed on the two outer sides of the collector in the thickness direction and arranged with the first negative electrode material and the second negative electrode material, and a second region formed in the center of the collector in the thickness direction and arranged with the first negative electrode material but not the above-mentioned second negative electrode material.
[0159] After immersing the above-mentioned negative electrode layer precursor in a skeleton forming agent liquid (equivalent to the third negative electrode material) prepared using the same process as in Example 1, the negative electrode precursor is heated and dried at 160°C to obtain the negative electrode of Example 2 as a negative electrode layer, which has a pair of first regions and a second region, the first region is formed on both outer sides of the thickness direction of the collector and is arranged with the first negative electrode material, the second negative electrode material and the third negative electrode material, and the second region is formed in the center of the thickness direction of the collector and is arranged with the first negative electrode material and the third negative electrode material but not the second negative electrode material.
[0160] In addition, the positive electrode of Example 2 has the same coating amount as that of Example 1 as that of Example 1, except that the coating amount is changed to 45 mg / cm 2 The other parts were prepared in the same manner as in Example 1. Furthermore, a battery was prepared in the same manner as in Example 1.
[0161] <Comparative Example 1>
[0162] A negative electrode was produced in the same manner as in Examples 1 and 2 except that the negative electrode material-free region (central space layer) was not provided during the production of the negative electrode, that is, except that the negative electrode material was applied to the entire current collector.
[0163] In addition, the positive electrode of Comparative Example 1 was modified from Example 1 to have a coating amount of 45 mg / cm 2 The other parts were prepared in the same manner as in Example 1. Furthermore, a battery was prepared in the same manner as in Example 1.
[0164] [Aging test]
[0165] An aging test was performed on each of the examples and comparative examples. The aging test was performed at a test environment temperature of 25°C.
[0166] [Durability test]
[0167] A cycle life test was conducted on each of the examples and comparative examples. The cycle life test was conducted at a test environment temperature of 25° C., a current density of 0.2 C-rate, and a cutoff potential of 2.5 to 4.2 V.
[0168] [Table 1]
[0169]
[0170] Note: “-” means there is no setting for this item.
[0171] Figure 7 This is a graph showing the relationship between the number of cycles and the discharge capacity of Examples 1 and 2 and Comparative Example 1.
[0172] according to Figure 7It is clear that according to this example, it was confirmed that a negative electrode for a nonaqueous electrolyte secondary battery and a nonaqueous electrolyte secondary battery including the negative electrode can be obtained, which can suppress structural degradation of the electrode and improve cycle durability.
[0173] Reference numerals
[0174] 1,1a: Negative electrode for non-aqueous electrolyte secondary battery
[0175] 11: Current Collector
[0176] 101,201,202: Negative electrode layer precursor
[0177] 12,12a: First negative electrode material
[0178] 13: Negative electrode active material
[0179] 14: Skeleton forming agent
[0180] 15: Conductive additive
[0181] 16: Adhesive
[0182] 17,17a: First area
[0183] 18,18a: Second area
[0184] 19,19a: Second negative electrode material
[0185] 20: The third negative electrode material
Claims
1. A negative electrode for a non-aqueous electrolyte secondary battery, comprising: a current collector composed of a porous metal body; A first negative electrode material is disposed in the pores of the porous metal body and comprises a negative electrode active material composed of a silicon-based material, a conductive aid, and a binder; and The second negative electrode material is arranged in the pores of the porous metal body and has a skeleton forming agent, wherein the skeleton forming agent includes a silicate having a siloxane bond; and the negative electrode for the non-aqueous electrolyte secondary battery has: a pair of first regions formed on both outer sides of the collector in the thickness direction and configured with the first negative electrode material and the second negative electrode material; and The second region is formed at the center of the current collector in the thickness direction and is provided with the second negative electrode material but not with the first negative electrode material.
2. A negative electrode for a non-aqueous electrolyte secondary battery, comprising: a current collector composed of a porous metal body; A first negative electrode material is disposed in the pores of the porous metal body and has a conductive additive; a second negative electrode material disposed in the pores of the porous metal body and comprising a negative electrode active material composed of a silicon-based material and a binder; and The third negative electrode material is arranged in the pores of the porous metal body and has a skeleton forming agent, wherein the skeleton forming agent includes a silicate having a siloxane bond; and the negative electrode for the non-aqueous electrolyte secondary battery has: a pair of first regions formed on both outer sides of the collector in the thickness direction and configured with the first negative electrode material, the second negative electrode material and the third negative electrode material; and The second region is formed at the center of the current collector in the thickness direction and is provided with the first negative electrode material and the third negative electrode material but not with the second negative electrode material.
3. The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein the skeleton-forming agent comprises a silicate represented by the following general formula (1): A2O·nSiO2……General formula (1) In the general formula (1), A represents an alkali metal, and n is 1.6 to 3.
9. 4 . The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1 , wherein the thickness of the second region is 0.5 to 15% of the thickness of the entire negative electrode. 5 . The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1 , wherein the porous metal body is a foamed metal body. 6 . A non-aqueous electrolyte secondary battery comprising the negative electrode for a non-aqueous electrolyte secondary battery according to claim 1 .
Citation Information
Patent Citations
Control method of idle speed
JP1986049147A
Resin composition
JP1988069818A
Skeleton-forming agent and negative electrode using same
CN108475787A
Composition for secondary battery negative electrode, negative electrode for secondary battery, and secondary battery
CN109980193A